The Existence Of Istano Melayu Kampung In Kampung In Koto Gadang Koto Anau Didtrict Lembang Jaya Solok District - Erza Safitri; Selvi Kasman; Edi Satria (Kirana Publisher (KNPub), 2023)
The problem of this research is to discuss the causes of the unmaintained Kampung Dalam Malay Palace and how the current condition of the Kampung Dalam Malay Palace in Koto Gadang Koto Anau is. This study aims to determine the existence of Kampung Dalam Malay Palace in Koto Gadang Koto Anau. The method used in this study is qualitative research, which uses data collection techniques through observation, interviews and documentation. The analysis carried out is collecting data, reducing data, displaying data and making conclusions. The results of the research and discussion show that the Malay Palace of Kampung Dalam was not maintained because Prince Novi Almana Bagindo Yang Dipituan did not want to receive assistance from the government because he was afraid that the palace would be taken over by the government because he thought that later the people of Koto Gadang Koto Anau would not be able to use The palace is a gathering place for big events. Whereas Istano Melayu Kampung Dalam, there are many cultural and tourist attractions of prehistoric heritage that are abandoned and not maintained, and the local community also pays little attention to them due to financial constraints. Meanwhile, the palace, which is now a museum, is not well-maintained, such as buildings that are old and not cleaned, lots of moss on the walls, even the items inside the palace are not maintained, due to the relatively large cost constraints to maintain the palace. The palace of Kampung Dalam Melayu which is now actually being rebuilt and not the old palace, because the original palace has been abandoned, the current palace building has not been completed, it can be seen from the condition of the palace.